NHS managers’ use of nursing workforce planning and deployment technologies: a realist synthesis - Christopher R Burton (Health Services and Delivery Research, 2018)
Background: Policy and reviews of health-care safety and quality emphasise the role of NHS managers in ensuring safe, good-quality patient care through effective staffing. Guidance requires that NHS managers combine professional judgement with evidence-based workforce planning and deployment tools and technologies (WPTs). Evidence has focused on the effectiveness of WPTs, but little is known about supporting their implementation, or the impact of using WPTs across settings. Objectives: The review answered the following question: ‘NHS managers’ use of workforce planning and deployment technologies and their impacts on nursing staffing and patient care: what works, for whom, how and in what circumstances?’. Design: A realist synthesis was conducted. A programme theory was formulated and expressed as hypotheses in the form of context, mechanisms and outcomes; this considered how, through using WPTs, particular conditions produced responses to generate outcomes. There were four phases: (1) development of a theoretical territory to understand nurse workforce planning and deployment complexity, resulting in an initial programme theory; (2) retrieval, review and synthesis of evidence, guided by the programme theory; (3) testing and refinement of the programme theory for practical application; and (4) actionable recommendations to support NHS managers in the implementation of WPTs for safe staffing. Participants: NHS managers, patient and public representatives and policy experts informed the programme theory in phase 1, which was validated in interviews with 10 NHS managers. In phase 3, 11 NHS managers were interviewed to refine the programme theory. Results: Workforce planning and deployment tools and technologies can be characterised functionally by their ability to summarise and aggregate staffing information, communicate about staffing, allocate staff and facilitate compliance with standards and quality assurance. NHS managers need to combine local knowledge and professional judgement with data from WPTs for effective staffing decisions. WPTs are used in a complex workforce system in which proximal factors (e.g. the workforce satisfaction with staffing) can influence distal factors (e.g. organisational reputation and potential staff recruitment). The system comprises multiple organisational strategies (e.g. professional and financial), which may (or may not) align around effective staffing. The positive impact of WPTs can include ensuring that staff are allocated effectively, promoting the patient safety agenda within an organisation, learning through comparison about ‘what works’ in effective staffing and having greater influence in staffing work. WPTs appear to have a positive impact when they visibly integrate data on needs and resources and when there is technical and leadership support. A collaborative process appears to be best for developing and implementing WPTs, so that they are fit for purpose. Limitations: The evidence, predominantly from acute care, often lacked detail on how managers applied professional judgement to WPTs for staffing decisions. The evidence lacked specificity about how managers develop skills on communicating staffing decisions to patients and the public. Conclusions and recommendations: The synthesis produced initial explanations of the use and impact of WPTs for decision-making and what works to support NHS managers to use these effectively. It is suggested that future research should further evaluate the programme theory. Study registration: This study is registered as PROSPERO CRD42016038132. Funding: The National Institute for Health Research Health Services and Delivery Research programme.